LIFEStyle, Prevention and Risk of Acute PaNcreatitis (LIFESPAN): protocol of a multicentre and multinational observational case–control study. Issue 1 (6th January 2020) - Koncz, Balázs; Darvasi, Erika; Erdősi, Dalma; Szentesi, Andrea; Márta, Katalin; Erőss, Bálint; Pécsi, Dániel; Gyöngyi, Zoltán; Girán, János; Farkas, Nelli; Papp, Maria; Fehér, Eszter; et al.
Abstract : Introduction: Acute pancreatitis (AP) is a life-threatening inflammatory disease of the exocrine pancreas which needs acute hospitalisation. Despite its importance, we have significant lack of knowledge whether the lifestyle factors elevate or decrease the risk of AP or influence the disease outcome. So far, no synthetising study has been carried out examining associations between socioeconomic factors, dietary habits, physical activity, chronic stress, sleep quality and AP. Accordingly, LIFESPAN identifies risk factors of acute pancreatitis and helps to prepare preventive recommendations for lifestyle elements. Methods and analysis: LIFESPAN is an observational, multicentre international case–control study. Participating subjects will create case and control groups. The study protocol was designed according to the SPIRIT guideline. Patients in the case group (n=1700) have suffered from AP (alcohol-induced, n=500; biliary, n=500; hypertriglyceridemiainduced, n=200; other, n=500); the control group subjects have no AP in their medical history. Our study will have three major control groups (n=2200): hospital-based (n=500), population-based (n=500) and aetiology-based (alcohol, n=500; biliary, n=500 and hypertriglyceridemia, n=200). All of them will be matched to the case group individually by gender, age and location of residence. Aggregately, 3900 subjects will be enrolled into the study. The study participants will complete a complex questionnaire with the help of a clinical research administrator/study nurse. Analysis methods include analysis of the continuous and categorical values. Ethics and dissemination: The study has obtained the relevant ethical approval (54175-2/2018/EKU) and also internationally registered (ISRCTN25940508 ). After obtaining the final conclusions, we will publish the data to the medical community and will also disseminate our results via open access. Trial registration number: ISRCTN25940508 ; Pre-results.